Symbolic Motif on Sepehri’s Poems - Morteza Ghasemi (مطالعات زبانی و بلاغی)
In line with personification and synesthesia, symbol is a significant characteristic of rhetorical level of Sohrab Sepehri’s style. By means of iteration, some of the symbols have been converted to an important and remarkable characteristic and are considered as motif. According to stylistical  investigations, words as “water, light and illumination, loneliness, void, nothing, lotus flower, apple, anemone flower, green and blue color” are symbolic motifs of “Hasht ketab”.   These symbols are extracted from three parts; nature, Zen-buddhism  and myth by which freshness and innovation are demonstrated in Sohrab Sepehri’s poem. After defining symbol and motif  in this article, symbolic motifs will be investigated by means of descriptive-analytical method, and according to poem’s contexture, the specific and accurate meaning of them will be expressed in different poems.